Perceptions of the graduates on the BA Sociology Program at the University of the Philippines Los Banos - Nelson, Gloria Luz M.; Quintos, Mark Anthony M. (2013)
The BA Sociology program was instituted in 1975 to complement the science and technology orientation of the University of the Philippines Los Banos. The program offers the choice to pursue the thesis, the all course work and practicum options to the students. The study aims to determine the perception of the graduates of BA Sociology Program. Two hundred thirty graduating students from 2005 to 2008 and 2010 to 2011 participated in the study. The results showed that the respondents chose Sociology for personal interest. Contrary to common perception that sociology graduates pursue for law degree, most of the BA sociology graduates, regardless of year of graduation intend to look for work while few would venture in putting their own business after graduation. It was found that BA sociology graduates have college educated parents and that there were more female graduates than male graduates. Graduates perceived that one of the strengths of the program is its capacity to enrich critical thinking skills of the graduates, closely akin to C. Wright Mills' "sociological imagination" which they think will be useful in development projects. On the other hand, its weakness is its failure to integrate the praxis and theoretically based on western ideas and offered limited opportunity for the practical application of these ideas in the Philippines setting. The newly approved revision of the program which was implemented in 2012 will satisfy this limitation.
Keywords: Perception